2016
DOI: 10.1186/s13027-016-0049-x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Porphyromonas gingivalis in esophagus and its association with the clinicopathological characteristics and survival in patients with esophageal cancer

Abstract: BackgroundMounting evidence suggests a causal relationship between specific bacterial infections and the development of certain malignancies. However, the possible role of the keystone periodontal pathogen, Porphyromonas gingivalis, in esophageal squamous cell carcinoma (ESCC) remains unknown. Therefore, we examined the presence of P. gingivalis in esophageal mucosa, and the relationship between P. gingivalis infection and the diagnosis and prognosis of ESCC.MethodsThe presence of P. gingivalis in the esophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
241
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(252 citation statements)
references
References 46 publications
4
241
3
4
Order By: Relevance
“…Porphyromonas gingivalis , is an oral Gram-negative, anaerobic periodontal bacterium (Hajishengallis et al, 2011) that was previously found to be overabundant in gingival squamous cell carcinoma (Gao et al, 2016; Katz et al, 2011; Whitmore and Lamont, 2014). When mice were intravenously inoculated with P. gingivalis , its levels in tumors are below the limit of detection both by culturing (~10 CFU/gr tissue) and qPCR (Figures 5D and 5E).…”
Section: Resultsmentioning
confidence: 99%
“…Porphyromonas gingivalis , is an oral Gram-negative, anaerobic periodontal bacterium (Hajishengallis et al, 2011) that was previously found to be overabundant in gingival squamous cell carcinoma (Gao et al, 2016; Katz et al, 2011; Whitmore and Lamont, 2014). When mice were intravenously inoculated with P. gingivalis , its levels in tumors are below the limit of detection both by culturing (~10 CFU/gr tissue) and qPCR (Figures 5D and 5E).…”
Section: Resultsmentioning
confidence: 99%
“…the species most strongly associated with severe periodontitis (30). A recent report revealed that Porphyromonas gingivalis was detected at a higher rate in ESCC tumor tissue, compared to adjacent normal and healthy control mucosa; moreover, Porphyromonas gingivalis presence was associated with ESCC lymph node metastasis and decreased survival time (39). More research is needed to determine whether periodontal disease and/or periodontal pathogens play a role in EAC/ESCC carcinogenesis, particularly since periodontal pathogen-EAC risk associations were inconsistent between the CPS-II and PLCO cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Another study using 16S rDNA sequencing technology demonstrated that, relative to controls, the gastric corpus microbiota of patients affected by esophageal squamous dysplasia and esophageal squamous cell carcinoma are enriched in Clostridiales and Erysipelotrichales, suggesting that gastric dysbiosis is involved in the progression from esophageal squamous dysplasia to squamous cell carcinoma 61. Gao et al 62. revealed that a specific microbiome Porphyromonas gingivalis infects the cancerous and adjacent esophageal mucosa of esophageal squamous cell carcinoma patients but not the healthy mucosa of controls, supporting a pathogenesis role of this organism in esophageal squamous cell carcinoma.…”
Section: Microbiome and Esophageal Squamous Cell Carcinomamentioning
confidence: 99%